Autism-Like Behavior in the Offspring of CYP11A1-Overexpressing Pregnant Rats - Pan, Tianying; Jiang, Chuan; Cheng, Juan; Xie, Jiang; Liu, Xinghui; Xu, Wenming; He, Guolin (Frontiers in Neuroscience, 2021)
Autism spectrum disorders (ASD) represent a complex group of neurodevelopmental disorders that are characterized by impaired social behavior and communication as well as repetitive behavior and restricted interests. Prenatal exposure to high levels of testosterone and preeclampsia are thought to be risk factors of ASD. We had previously reported that overexpression of the mitochondrial cholesterol side-chain cleavage enzyme (CYP11A1) could lead to both preeclampsia-like symptoms and increased testosterone levels in pregnant rats. In this study, we investigated the association between high CYP11A1 levels in pregnant rats and autism-like behavior in their offspring. Timed-pregnant Sprague-Dawley (SD) rats were injected with CYP11A1 gene-carrying adenoviruses on gestational day 8.5, and their offspring were then compared with those from timed-pregnant control SD rats. Compared with their control counterparts, the offspring of the CYP11A1-ovexpressing dams displayed more symptoms of anxiety and spent less time in social interactions and more time in self-grooming and rearing, all indicators of autism-like behavior. Sequencing of the transcriptome in primary microglia from the offspring of CYP11A1-overexpressing dams revealed that immune pathways were highly activated, and the gamma-aminobutyric acid type A (GABAA) receptor genes were among the top differentially expressed genes. Using primary microglia cultures generated from neonatal rats, tumor necrosis factor-alpha expression was found to be elevated in the cells transfected with CYP11A1¬-carrying adenoviruses. Additionally, the offspring of CYP11A1-overexpressing dams displayed dysregulated GABAA receptor expression. Taken together, these results suggest that abnormal CYP11A1 gene expression in pregnant rats could lead to microglial immune activation and dysregulated GABAA receptor expression in their offspring and thereby anxiety and autism-related behavior. Our study suggests that the pathways regulated by CYP11A1 could be promising preventative and therapeutic targets for ASD.